2004
DOI: 10.1097/01.tp.0000140884.71571.bc
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Gene Polymorphisms and Risks of Acute Rejection and Delayed Graft Function after Kidney Transplantation

Abstract: Our results confirm that cytokine gene polymorphisms influence the outcome of kidney transplantation. Our data especially identify the TNF-alpha -308AA-genotype as a factor predisposing for AR episodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 40 publications
4
37
3
Order By: Relevance
“…In concordance with our observations, a recent study in a similar population [27] found patients homozygous for the -592A allele had a higher risk of developing BPAR (OR: 2.2, 95% CI [1.0-4.7]; P = 0.072). Conversely, a report in 209 transplant recipients did not find any association between C-592A polymorphism and BPAR [44] although this study only considered BPAR during the first 30 days post-transplantation under a different treatment regimen to that in the CAESAR study.…”
Section: Il-10supporting
confidence: 81%
See 2 more Smart Citations
“…In concordance with our observations, a recent study in a similar population [27] found patients homozygous for the -592A allele had a higher risk of developing BPAR (OR: 2.2, 95% CI [1.0-4.7]; P = 0.072). Conversely, a report in 209 transplant recipients did not find any association between C-592A polymorphism and BPAR [44] although this study only considered BPAR during the first 30 days post-transplantation under a different treatment regimen to that in the CAESAR study.…”
Section: Il-10supporting
confidence: 81%
“…However, it should be noted that we combined data from GA heterozygotes and AA homozygotes on account of the small number of AA homozygotes in our sample. As a result, we cannot fully corroborate the results of Alakulppi et al [27] that described a significant association with AA homozygotes. There have also been conflicting reports about the TNF-a G-308 allele and the risk of rejection when linked to the IL-10-AA polymorphism [26,27,44].…”
Section: Tnf-acontrasting
confidence: 55%
See 1 more Smart Citation
“…Other authors that have tested this locus in donors did not find an association for acute rejection (see Table 2) in relatively large (N100 cases) [42,43] or in smaller [44][45][46] studies, thus it may be specific for the immediate post-transplant period, and for solely cadaver donors. Despite a small case number for the phenotype studied (n = 39, graft loss), Müller-Steinhardt and colleagues had complete 3 year data for their cohort of 158 kidney recipients [47].…”
Section: Positive Associations In Donor and Recipient Cohortsmentioning
confidence: 89%
“…[31][32][33] It also has been demonstrated that the TNF-α-308 A allele could increase the risk of acute rejection. 5,[34][35][36][37] Interestingly, HLA-matched allogeneic donorrecipient pairs often are mismatched for microsatellite markers in the class III region, leading to complications after allogeneic hematopoietic stem cell transplants. 38,39 These findings suggest that there are genes in the MHC other than HLA, such as TNF-α, that affect transplant outcome.…”
Section: Discussionmentioning
confidence: 99%